The Impact of Unionization in the Agricultural Sector: Farmer Perceptions and Behavior - HAMZAOĞLU, NAZİFE MERVE (Hacettepe Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dekanlığı, 2023)
For centuries, agriculture has been one of the vital sectors in economic development; its role in developing economies and rural development is still inevitable. Rising food and energy prices and the negative effects of climate change can be more problematic for middle-smallholder farmers or family enterprises and low-qualified farmworkers. To overcome them, unionization and cooperatives in agriculture may present a viable option. Unionization in agriculture can be a solution for vulnerable parts of agriculture, such as workers who are exploited by working cheap and long hours and small and family businesses in a market where cooperatives are disrupted. This study focuses on the impact of unionization in the agricultural market by exploring farmer behavior. World Values Survey Data (Wave 7) was applied to reveal the factors affecting farmers' perception of the economic and social factors from different countries by segmenting union members and non-members using binomial logistic regression models. The findings show that unionized farmers have different motivations than non-members. Income targeting policies are essential to support agri-business owners.
Tarım Sektöründe Sendikalaşmanın Etkisi: Çiftçi Algıları ve Davranışı
Keywords: Unionization; Farmer Behavior; Agriculture; Perceptions